Early-life iron deficiency persistently disrupts affective behaviour in mice. (12th December 2023) - Gundacker, Anna; Glat, Micaela; Wais, Jonathan; Stoehrmann, Peter; Pollak, Arnold; Pollak, Daniela D.
Abstract: Background/Objective: Iron deficiency (ID) is the most common nutrient deficiency, affecting two billion people worldwide, including about 30% of pregnant women. During gestation, the brain is particularly vulnerable to environmental insults, which can irrevocably impair critical developmental processes. Consequently, detrimental consequences of early-life ID for offspring brain structure and function have been described. Although early life ID has been associated with an increased long-term risk for several neuropsychiatric disorders, the effect on depressive disorders has remained unresolved. Materials and methods: A mouse model of moderate foetal and neonatal ID was established by keeping pregnant dams on an iron-deficient diet throughout gestation until postnatal day 10. The ensuing significant decrease of iron content in the offspring brain, as well as the impact on maternal behaviour and offspring vocalization was determined in the first postnatal week. The consequences of early-life ID for depression- and anxiety-like behaviour in adulthood were revealed employing dedicated behavioural assays. miRNA sequencing of hippocampal tissue of offspring revealed specific miRNAs signatures accompanying the behavioural deficits of foetal and neonatal ID in the adult brain. Results: Mothers receiving iron-deficient food during pregnancy and lactation exhibited significantly less licking and grooming behaviour, while active pup retrieval and pup ultrasonic vocalizations were unaltered. Adult offspring with a history of foetal and neonatal ID showed an increase in depression- and anxiety-like behaviour, paralleled by a deranged miRNA expression profile in the hippocampus, specifically levels of miR200a and miR200b. Conclusion: ID during the foetal and neonatal periods has life-long consequences for affective behaviour in mice and leaves a specific and persistent mark on the expression of miRNAs in the brain. Foetal and neonatal ID needs to be further considered as risk factor for the development of depression and anxiety disorders later in life. Key Messages: Marginal reduction of gestational alimentary iron intake decreases brain iron content of the juvenile offspring. Early-life ID is associated with increased depression- and anxiety-like behaviour in adulthood. Reduction of maternal alimentary iron intake during pregnancy is reflected in an alteration of miRNA signatures in the adult offspring brain.